Human Sciences? - Capasso, Lorenzo (Medicina Historica, 2020)
This paper is in response to the Editorial by Professor Armocida about the theme of Human Sciences in medical education (Medical Humanities). The author thinks that this is a central topic and he reckons that all the involved subjects must gain consideration and be part of the medical curriculum in order to improve and widen not only the knowledges of undergraduate students, but also their skills. The author concludes suggesting a strong shift in medical education, promoting the introduction of a curriculum including medical humanities at the expenses of clinical subjects and to move practical training from hospitals to territorial services in order to learn how to face chronicity, comorbidity and disability.